Optimizing IPAS Learning Outcomes Thru the Use of Assemblr Edu for Fifth Grade Elementary School Students - Nirma Rhokhmatika; Abdul Karim; Sati Sati (FKIP - Universitas Riau, 2026)
Low learning outcomes in Natural and Social Sciences (IPAS) remain a challenge in the learning process at SD Negeri 2 Kerticala. This study aims to examine the effect of Assemblr Edu on fifth-grade students' science learning outcomes. A quantitative approach with a one-group pretest-posttest experimental design was used. The population consisted of 265 students, and the sample involved 25 fifth-grade students selected through simple random sampling. Data were collected through tests, questionnaires, and observations. Test score data were analyzed using normality, homogeneity, hypothesis, and N-Gain tests. The results showed that the data were normally distributed and homogeneous. A paired t-test showed a significant difference between the pretest and posttest scores (t = 14.328 > 2.064). The average score increased from 54.60 to 87.20, with an increase of 32.60 points. Furthermore, the N-Gain score of 0.7106 (71%) was categorized as high. Student responses were also very positive, with an average questionnaire score of 79.6. These findings indicate that Assemblr Edu effectively improves students' science learning outcomes. The novelty of this study lies in the application of Assemblr Edu media to the topic of environmental change combined with concrete images among fifth-grade elementary school students.